2018
DOI: 10.1155/2018/1396216
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioural Therapy through PowerPoint: Efficacy in an Adolescent Clinical Population with Depression and Anxiety

Abstract: Background Limited help-seeking behaviours, among adolescents with mental health concerns and many barriers to accessing mental health services, make innovative approaches to administering mental health therapies crucial. Therefore, this study evaluated the efficacy of e-CBT given via PowerPoint slides to treat adolescents with anxiety and/or depression. Method 15 adolescents referred to an outpatient adolescent psychiatry clinic to treat a primary DSM-IV diagnosis of anxiety and/or depression chose between 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Young people also highlighted that working on their sense of self might feel less pressured in an online format. Interestingly, this supports one study that found better effects for CBT in an online format [ 63 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Young people also highlighted that working on their sense of self might feel less pressured in an online format. Interestingly, this supports one study that found better effects for CBT in an online format [ 63 ].…”
Section: Resultssupporting
confidence: 87%
“…Improvement in depression was marked by increases in global self-worth and some subscales. Intervention studies Study N (depressed) % Female Age Sample Self Terminology Self Measure Depression Status Intervention Effects Alavi et al (2018) [ 63 ] 15 86 14–17 Outpatient facility Self-concept BSCI-Y Diag. (DSM-IV) Face to face vs e-CBT Mixed effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E-CBT content can be conveniently accessed anytime and anywhere, thereby providing flexible access to care, even for people who live in remote areas. A major benefit of e-CBT is that by delivering predesigned therapy content, clinicians can skip repeating similar general concepts to multiple patients and reduce their time commitment to a fraction of that in in-person therapy [ 12 , 13 ]. This not only reduces the cost of care delivery, but also allows more people to receive care from existing clinical resources and shortens waiting times.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage to using e-CBT as a treatment delivery modality is that some individuals might not have access to the necessary technology (eg, phones, tablets, or laptops) or proper internet connectivity. Furthermore, there are different methods of delivering e-CBT, which range from unguided self-help [ 14 , 15 ] to guided programs that consist of a standardized content delivery modality with support from a mental health professional [ 12 , 13 , 16 ]. Although these different methods have been shown to be effective to some extent, their efficacy varies depending on the level of care provider engagement during the therapy process [ 17 ].…”
Section: Introductionmentioning
confidence: 99%